The Ped-APS registry: The antiphospholipid syndrome in childhood - Avčin, Tadej; Cimaz, R.; Rozman, B.; Cervera, Ricard; Ravelli, Angelo; Martini, Alberto; Meroni, Pier Luigi; Garay, Stella; Sztajnbok, Flavio R.; Silva, Clovis A.; Campos, Lucia M.; Saad-Magalhaes, Claudia [UNESP]; et al. (SAGE Publications, 2009)
In recent years, antiphospholipid syndrome (APS) has been increasingly recognised in various paediatric autoimmune and nonautoimmune diseases, but the relatively low prevalence and heterogeneity of APS in childhood made it very difficult to study in a systematic way. The project of an international registry of paediatric patients with APS (the Ped-APS Registry) was initiated in 2004 to foster and conduct multicentre, controlled studies with large number of paediatric APS patients. The Ped-APS Registry is organised as a collaborative project of the European Forum on Antiphospholipid Antibodies and Juvenile Systemic Lupus Erythematosus Working Group of the Paediatric Rheumatology European Society. Currently, it documents a standardised clinical, laboratory and therapeutic data of 133 children with antiphospholipid antibodies (aPL)-related thrombosis from 14 countries. The priority projects for future research of the Ped-APS Registry include prospective enrolment of new patients with aPL-related thrombosis, assessment of differences between the paediatric and adult APS, evaluation of proinflammatory genotype as a risk factor for APS manifestations in childhood and evaluation of patients with isolated nonthrombotic aPL-related manifestations. © The Author(s), 2009.
Keywords: Antiphospholipid antibodies; Antiphospholipid syndrome; Paediatrics; phospholipid antibody; antiphospholipid syndrome; deep vein thrombosis; genotype; human; pediatrics; prevalence; priority journal; prognosis; register; risk assessment; risk factor; single nucleotide polymorphism; systemic lupus erythematosus; vein thrombosis; Antiphospholipid Syndrome; Child; Humans; Registries; Thrombosis